2015
DOI: 10.1016/j.apmr.2015.02.029
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Pressure Ulcers in Individuals With Spina Bifida

Abstract: Objective To describe factors associated with pressure ulcers in individuals with spina bifida (SB) enrolled in the National Spina Bifida Patient Registry (NSBPR). Design Unbalanced longitudinal multicenter cohort study. Setting Nineteen SB clinics. Participants Individuals with SB (N=3153) enrolled in 19 clinic sites that participate in the NSBPR. Interventions Not applicable. Main Outcome Measures Pressure ulcer status (yes/no) at the annual visit between 2009 and 2012. Results Of 3153 total part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 21 publications
5
44
1
Order By: Relevance
“…Kim et al () documented that 19% of individuals reported a pressure ulcer at their most recent annual clinic visit. Adjusting for type of SB, SB clinic, and age group, the authors found that the level of the lesion, male sex, use of a wheelchair, urinary incontinence, presence of a shunt for hydrocephalus, above the knee orthopedic surgery, and recent surgery were associated with skin injury (Kim et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Kim et al () documented that 19% of individuals reported a pressure ulcer at their most recent annual clinic visit. Adjusting for type of SB, SB clinic, and age group, the authors found that the level of the lesion, male sex, use of a wheelchair, urinary incontinence, presence of a shunt for hydrocephalus, above the knee orthopedic surgery, and recent surgery were associated with skin injury (Kim et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…A description of the methods for developing and refining a urologic protocol for newborns and young children with spina bifida has also been published [6]. A paper titled, “Factors Associated with Pressure Ulcers in Individuals with Spina Bifida” [7] provides an example of how Registry data have been used to identify and promote improved care, and will be described in more detail below.…”
Section: Methodsmentioning
confidence: 99%
“…Urinary incontinence has a devastating impact on QoL as it demonstrates loss of bodily control in its most inconvenient and unpleasant way, make LUT care the most challenging issue in the patient's daily life, and can itself drive patients into depression [198][199][200]. Furthermore, urinary incontinence can negatively affect the skin due to frequent contact with urine and/or the necessity to wear pads or diapers which facilitates the development of wounds/ulcerations and dermal infections [201][202][203]. Despite the frequent association of NDO with urinary incontinence [204], adequate treatment of NDO alone may be either insufficient to prevent urinary incontinence or even evoke urinary incontinence.…”
Section: Restoration Of Urethral Urine Storage Functionmentioning
confidence: 99%